Struktur, Makna, dan Fungsi Ungkapan Kepercayaan Rakyat di Nagari Solok Ambah Kabupaten Sijunjung - Fitri, Hayatul; Nst., Bakhtaruddin; Hamidin, Hamidin (Universitas Negeri Padang, 2012)
This article was written with the purpose of describing the structure, meaning and function of an expression of folk handicraft in Nagari Solok Ambah Sijunjung district. The data in this study is in the form of structure, meaning, and function expression of the people's trust. Based on the discussion can be concluded first, the structure of people's expression of confidence in a two-part and three-part Second, the meaning of an expression of the people is the true meaning of the expression of these beliefs to be conveyed through the expression of belief. Third, the function of an expression of the people for the people is a Nagari Solok Ambah as a thickener religious emotions or beliefs, as an educational tool or teenagers, as